Pengaruh Flash Sale, Bebas Biaya Pengiriman, dan Hedonic Shopping Motivation terhadap Impulse Buying pada Pengguna Shopee di Gresik - Kusuma, Ramadhan Alim; Nurhadi, Nurhadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
E-commerce in Indonesia is now widely established and continues to grow. One of them is Shopee. Shopee is one of the e-commerce sites most frequently visited by Indonesian people. Shopee has various forms of sales promotions, such as flash sales, free shipping, and so on This study aims to determine the effect of flash sales, free shipping, and hedonic shopping motivation simultaneously and partially on impulse buying among Shopee users in Gresik Regency. The population in this research is all consumers who have carried out the purchasing process through Shopee e-commerce, domiciled in Gresik City. The sampling technique used in this study was purposive sampling with the criteria of Shopee consumers domiciled in Gresik City, and consumers with a minimum age of 15 years. Data collection techniques in research use E-Questionnaires (Electronic Questionnaires) via Google Form. The data analysis technique used in this research is multiple linear analysis. The results of testing the hypothesis using the f test show that simultaneously flash sales (X1), free shipping (X2), and hedonic shopping motivation (X3) have a significant effect on Impulse Buying (Y). Meanwhile the results of the t test show that a) Partially the flash sale variable (X1) has a significant effect on impulse buying, b) Partially the free shipping variable (X2) has no significant effect on impulse buying, c) Partially the hedonic shopping motivation variable ( X3) has a significant effect on impulse buying.